Belief in Just World and Life Satisfaction in Undergraduate Students: Cross Cultural Study in Indonesia and China - Endah Puspita Sari; Ahmad Zain Fahmi; Nadhila Safitri; Muhammad Garlianka Wangsadikrama; Yifang Wu; Qianqian Lu (Journal of Educational, Health and Community Psychology, 2021)
Â The purpose of this research was to compare cross-culturally between belief in a just world and life satisfaction among students in China and Indonesia. Subjects in this study were 194 students in China and 112 students in Indonesia who vary in religion, race, and study field. This research used three scales to collect the data, the Global Belief in Just World Scale, Personal Belief in Just World Scale, and the Satisfaction with Life Scale. The correlation test showed that for Indonesian subjects, the strong correlation is between Personal Belief in Just World and Life Satisfaction (r = 0.330, p = 0.000). And for China subjects, the strong correlation is between Personal Belief in Just World and Life Satisfaction (r = 0.412, p = 0.000). From the comparative test, Global Belief in Just World in Indonesia subjects was higher than in China subjects (h2 = 0.066, p = 0.000). A more detailed explanation will be provided in this paper.Â